2017
DOI: 10.1093/ndt/gfx246
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 inhibition attenuates the progressive phenotypes of Alport syndrome mouse model

Abstract: STAT3 inhibition significantly ameliorated the renal dysfunction in AS mice. Our finding identifies STAT3 as an important regulator in AS progression and provides a promising therapeutic target for AS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 33 publications
0
34
0
Order By: Relevance
“…Glomerular dysfunction and resulting albuminuria further stimulates proximal tubule damage and eventual fibrosis, which progresses to renal failure (72). Yokota et al (103) investigated STAT3 activation in Alport syndrome and found increased pSTAT3 (Tyr 705 ) in both isolated glomeruli and the renal cortex of a mouse model of Alport syndrome, with accompanying increases in proinflammatory STAT3 target genes (Table 1). They tested whether or not STAT3 inhibition could ameliorate renal dysfunction in a mouse model of Alport syndrome.…”
Section: Alport Syndromementioning
confidence: 99%
“…Glomerular dysfunction and resulting albuminuria further stimulates proximal tubule damage and eventual fibrosis, which progresses to renal failure (72). Yokota et al (103) investigated STAT3 activation in Alport syndrome and found increased pSTAT3 (Tyr 705 ) in both isolated glomeruli and the renal cortex of a mouse model of Alport syndrome, with accompanying increases in proinflammatory STAT3 target genes (Table 1). They tested whether or not STAT3 inhibition could ameliorate renal dysfunction in a mouse model of Alport syndrome.…”
Section: Alport Syndromementioning
confidence: 99%
“…STAT3 and IL6 were found to be increased in mice with Alport syndrome before anti-miR-21 treatment; the group, therefore, investigated the impact of STAT3 and IL6 inhibitors in Alport mice. They found that STAT3 inhibition reduced proteinuria, whereas IL6 inhibition had no effect on this metric of glomerular function [39]. This is not the only treatment that the group have tested in Alport mice; bromide supplementation was also tried, as Billy Hudson had shown bromide to be important for type IV collagen network formation [40].…”
Section: Basic Sciencementioning
confidence: 99%
“…LLC., USA) following the recommended protocol. To evaluate the glomerulosclerosis severity, more than 50 random glomeruli per mouse were scored based on the following criteria as reported previously 43 , 0: no lesion, 1: expansion of mesangial area, 2: expansion of Bowman’s epithelial cells, adhesion of glomeruli and Bowman’s capsule and partial sclerosis, 3: sclerotic area in 50–75% of glomeruli, and 4: sclerotic area in 75–100% of glomeruli. In addition, 10 random fields per mouse were captured and protein cast area (%) was calculated by the ratio to tissue area.…”
Section: Methodsmentioning
confidence: 99%